HIV/AIDS knowledge and attitudes towards HIV and condom use among internally displaced Libyan males. Is there a need to implement sex education? - Fauzi Elamouri; Jürgen Kurt Rockstroh; Worapath Kratoo; Yuka Miyahara; Tepanata Pumpaibool (HIV Research & Clinical Practice)
Background Displacement has been associated with an increased risk of HIV transmission. In light of the lack of data from Libya on sexual behavior and HIV/AIDS knowledge, the effort was undertaken to assess HIV/AIDS knowledge and attitudes towards HIV and condom use in Libyan internally displaced males (IDPs) in Tripoli. Methods Cross-sectional study design using purposive sampling to identify internally displaced Libyan males from five camps in Tripoli. HIV/AIDS knowledge, attitudes towards HIV and condom use, and prevention practices were evaluated through a self-administered, close/ended anonymous questionnaire in Arabic. Results The study population consisted of 390 participants, all Muslims, with a mean age of 32.81 years (SD = 8.93). Overall, the average HIV and prevention knowledge score was 6.34 (SD = 1.98). The majority of the respondents thereby had an insufficient or low knowledge’ level of HIV and prevention knowledge (58.70%). The mean attitude score indicated overall a negative attitude towards condom use (Mean = 32.60, SD = 7.97). Conclusions This is the first biobehavioral survey among IDPs in Libya demonstrating a low level of HIV and prevention knowledge as well as a prevailing negative attitude level of HIV/AIDS and condom use.